2014
DOI: 10.4236/oju.2014.410021
|View full text |Cite
|
Sign up to set email alerts
|

Urologic Complications after Gynaecologic and Obstetric Surgery at the Urology-Andrology Teaching Clinic of Teaching Hospital of Cotonou

Abstract: Objective: To study the epidemiology and current trend in the management of urologic complications following obstetric and gynaecologic surgeries at CUUA University hospital of Cotonou. Patients and Methods: It was a retrospective study of patients referred with urologic complications following obstetric and gynaecological surgeries. The study took place at the Teaching Clinic of Urology Andrology at CNHU of Cotonou between April 1, 2008 and March 31, 2013. Results: Fortyone patients were studied. They represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…This study showed that 85.9% patients were referred from clinics while 14.1% patients were referred from district hospitals, similar to 73.2% and 17.1% respectively reported by Pascalet al 8 The incidence of re-lapartomy in our study was 3.7% which was more than 0.80% reported by Alam et al 9 Indication of repeat surgery in this study was internal hemorrhage 11.88%, uncontrolled PPH 6.67%, rectus sheath hematoma 11.11%. The result is near to that of Akhteret al 10 who found it 48.99%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study showed that 85.9% patients were referred from clinics while 14.1% patients were referred from district hospitals, similar to 73.2% and 17.1% respectively reported by Pascalet al 8 The incidence of re-lapartomy in our study was 3.7% which was more than 0.80% reported by Alam et al 9 Indication of repeat surgery in this study was internal hemorrhage 11.88%, uncontrolled PPH 6.67%, rectus sheath hematoma 11.11%. The result is near to that of Akhteret al 10 who found it 48.99%.…”
Section: Discussionsupporting
confidence: 89%
“…In this hospital setting 574 (85.03%) patients were improved by conservative treatment,405 (60%) patients required at least one unit of blood transfusion. 41 (45.55%) cases genitourinary fistula were repaired overall success rate was (90.9%).It was similar to a study by Pascal HP et al 12…”
Section: Discussionsupporting
confidence: 83%
“…Health workers who perform surgeries lack understanding of the anatomical link between the urinary and genital tracts. 26 Preventing blind blood vessel clamping, working closely to pathology, identifying the ureteral course prior to dissection, careful movement from the operation site, and brief diathermy treatments can all help to reduce ureteral injuries. 27 Surgically, the ureteric injuries are challenging to diagnose.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to ureteral injuries, bladder injuries have been found to occur 2-3 times more frequently. 15 Post surgery, urogenital fistula formation and leakage in bladder are painful for patient and cause the surgeon concern and a sense of failure. Similar to the development of anuria right after surgery, this condition necessitates rapid care for patient.…”
Section: Introductionmentioning
confidence: 99%
“…Gynaecological surgeries have been reported to be responsible for 75% of the injuries to the ureter. At the same time, it has been noted that bladder injuries are 2 to 3 times more frequent than ureteral injuries 2 .…”
Section: Introductionmentioning
confidence: 99%